The Effects of Social Media on Political Participation and Candidate Image Evaluations in the 2012 Iowa Caucuses. (November 2013) - Dimitrova, Daniela V.; Bystrom, Dianne
Much academic debate has centered on the impact of new technologies on democracy. This study examines the effects of social media on political participation and candidate image evaluations in the first-in-the-nation Iowa caucuses. Multivariate analyses show that social media have no effects on likelihood of caucus attendance but influence perceptions of candidate traits among the sample of Iowans drawn here. The study also addresses the role of traditional media as channels for political information during the caucuses.